An Overview of Extra Pulmonary Tuberculosis in Smear Negative Cases and their Analysis: Life Sciences-Clinical Biology for Effective Treatment - TalluriRameshwari K R; Jayashree K; Anuradha K; Raghuraj Singh Chouhan; Sumana K (International Journal of Life Science and Pharma Research, 2022)
Mycobacterium tuberculosis (MTB), a bacterium which causes the tuberculosis disease, is one of the most trounce disease in the country. It mainly affects the lungs and other parts of the body. Currently smear-positive cases are further confirmed through chest radiography for PTB. These cases are further subjected for short course chemotherapy (SCC), followed by first line primary drugs, a scheme undertaken by National Tuberculosis Programme to overcome PTB infection. However, the identification of infection through smear-negative results are challenging as the cases may become positive over the time and progresses to cause the Extra Pulmonary Tuberculosis (EPTB). Such infections are asymptomatic and referred to as latent infection, where, MTBremains stable for many years at a specific site and later activates. Worldwide about 10-25% of latent infections progress to an active disease and if undiagnosed, the mortality rate may reach up to 50%. Twenty five percent of EPTB infection differs from organ to organ of the body. However, in such cases, diagnosis may be elusive and is usually delayed. The proper identification of infection that strongly focuses on the infection of either i.e., TB or EPTB is the need of the hour. The diagnosis of EPTB will be elusive, necessitating a high index of suspicion over TB or EPTB. However, smear-negative cases may be positive for EPTB infection, where the suspects are to be further subjected for molecular methods of EPTB detection and confirmation.